Language Models in Sociological Research: An Application to Classifying Large Administrative Data and Measuring Religiosity. Issue 1 (February 2022) - Jensen, Jeffrey L.; Karell, Daniel; Tanigawa-Lau, Cole; Habash, Nizar; Oudah, Mai; Fairus Shofia Fani, Dhia
Computational methods have become widespread in the social sciences, but probabilistic language models remain relatively underused. We introduce language models to a general social science readership. First, we offer an accessible explanation of language models, detailing how they estimate the probability of a piece of language, such as a word or sentence, on the basis of the linguistic context. Second, we apply language models in an illustrative analysis to demonstrate the mechanics of using these models in social science research. The example application uses language models to classify names in a large administrative database; the classifications are then used to measure a sociologically important phenomenon: the spatial variation of religiosity. This application highlights several advantages of language models, including their effectiveness in classifying text that contains variation around the base structures, as is often the case with localized naming conventions and dialects. We conclude by discussing language models' potential to contribute to sociological research beyond classification through their ability to generate language.